2018
DOI: 10.1038/s41598-018-19785-1
|View full text |Cite
|
Sign up to set email alerts
|

Grazing and climate effects on soil organic carbon concentration and particle-size association in northern grasslands

Abstract: Grasslands cover more than 40% of the terrestrial surface of Earth and provide a range of ecological goods and services, including serving as one of the largest reservoirs for terrestrial carbon. An understanding of how livestock grazing, influences grassland soil organic carbon (SOC), including its concentration, vertical distribution and association among soil-particle sizes is unclear. We quantified SOC concentrations in the upper 30 cm of mineral soil, together with SOC particle-size association, within 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 38 publications
(36 reference statements)
2
57
0
1
Order By: Relevance
“…In moist, warm climates and those populated by C 4 grasses, soil C increased for all grazing intensities, but in arid regions, only low or moderate intensities increased SOC, indicating site specificity in SOC response to grazing intensity. Greater soil C accumulation in higher rainfall environments has been cited by others (Chen et al, 2018;Hewins et al, 2018) and was attributed to greater species richness and belowground biomass in mesic than dry environments (Chen et al, 2018). A synthesis of 47 experimental contrasts in 17 studies showed that grazing effects were variable and highly context dependent, a function of climate, soil, forage species, and grazing intensity (McSherry and Ritchie, 2013).…”
Section: Presence Of Legumesmentioning
confidence: 89%
See 2 more Smart Citations
“…In moist, warm climates and those populated by C 4 grasses, soil C increased for all grazing intensities, but in arid regions, only low or moderate intensities increased SOC, indicating site specificity in SOC response to grazing intensity. Greater soil C accumulation in higher rainfall environments has been cited by others (Chen et al, 2018;Hewins et al, 2018) and was attributed to greater species richness and belowground biomass in mesic than dry environments (Chen et al, 2018). A synthesis of 47 experimental contrasts in 17 studies showed that grazing effects were variable and highly context dependent, a function of climate, soil, forage species, and grazing intensity (McSherry and Ritchie, 2013).…”
Section: Presence Of Legumesmentioning
confidence: 89%
“…A global review and meta-analysis of 83 studies of extensively managed grasslands found an interaction of grazing intensity and regional climate for soil C accumulation (Abdalla et al, 2018). Greater soil C accumulation in higher rainfall environments has been cited by others (Chen et al, 2018;Hewins et al, 2018) and was attributed to greater species richness and belowground biomass in mesic than dry environments (Chen et al, 2018). Greater soil C accumulation in higher rainfall environments has been cited by others (Chen et al, 2018;Hewins et al, 2018) and was attributed to greater species richness and belowground biomass in mesic than dry environments (Chen et al, 2018).…”
Section: Presence Of Legumesmentioning
confidence: 95%
See 1 more Smart Citation
“…14 Climatic variables such as rainfall and temperature can also be derived from WorldClim database (global climate layers) at a spatial resolution of about 1 km 2 . 23 The use of DEMs derived from satellite missions such as Light Detection and Ranging (LiDAR) and Shuttle Radar Topography Mission (SRTM) for terrain analysis has become particularly popular due to their relatively high resolutions. 24 Hence, the development of models with SRTM and LiDAR-derived topographic metrics in concert with selected bioclimatic variables could benefit studies characterised by limited observations and can be used to produce continuous SOC distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Jones et al [39] found that soil respiration from plots receiving manure was up to 1.6 times larger than CO2 release from control plots, and up to 1.7 times larger compared to inorganic treatments (p<0.05). Hewins et al [40] found that while climate had the largest impact on SOC concentrations, grazing increased C concentration more in mesic grazing lands of Alberta, Canada. Teague et al [41] indicated that grass cover under proper management is highly effective in reducing soil erosion and in increasing SOC stocks.…”
Section: Soc Nutrient Cycle and Greenhouse Has Emissions As A Functimentioning
confidence: 99%